2021
DOI: 10.1002/gch2.202000115
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Nanomaterials to COVID‐19 Management: A Systematic Review on Antiviral/Virucidal Agents and Mechanisms of SARS‐CoV‐2 Inhibition/Inactivation

Abstract: A novel beta-coronavirus, the novel coronavirus (SARS-CoV-2), or the severe acute respiratory syndrome coronavirus 2, was described as the causative agent of the pneumonia outbreak of coronavirus disease 2019 (COVID-19), first reported in December 2019 in a local seafood market of Wuhan, Hubei province, China. [1,2] The same beta-coronavirus genus of SARS-CoV-2 was earlier the causative of viral pneumonia pandemics caused by severe acute respiratory syndrome coronavirus (SARS-CoV) and the Middle East respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 109 publications
(164 reference statements)
2
52
0
1
Order By: Relevance
“… 144 Eco-friendly nonspherical nanocellulose nanofiber is synthesized which is a sustainable, nontoxic, low-cost, and biocompatible carrier with antimicrobial effects. 145 Antibodies conjugated to biomaterial-based NP surfaces allow efficient and effective inflammatory marker removal caused by the cytokine storm. Chitosan, hyaluronic acid, PLGA, and mesoporous silica NPs can be used for surface conjugation to reduce the burden of SARS-CoV-2 cytokine storms.…”
Section: Nanostructure-based Covid-19 Managementmentioning
confidence: 99%
“… 144 Eco-friendly nonspherical nanocellulose nanofiber is synthesized which is a sustainable, nontoxic, low-cost, and biocompatible carrier with antimicrobial effects. 145 Antibodies conjugated to biomaterial-based NP surfaces allow efficient and effective inflammatory marker removal caused by the cytokine storm. Chitosan, hyaluronic acid, PLGA, and mesoporous silica NPs can be used for surface conjugation to reduce the burden of SARS-CoV-2 cytokine storms.…”
Section: Nanostructure-based Covid-19 Managementmentioning
confidence: 99%
“…In the same case, Carvalho et al reported the most common NMs with anti‐coronavirus activity against animal and human COVs (Fig. 1 ) in a systematic review study [ 24 ]. It is worth bearing in mind, nanobiocides-based materials are metal and metal oxides, engineered/synthesized NMs, and natural antibacterial substances showing strong antimicrobial activity through diverse mechanisms [ 25 ].…”
Section: Introductionmentioning
confidence: 97%
“…These strategies include the development of nanomaterial-based (i) preventive measures and disinfectants, (ii) diagnostic tools for rapid, sensitive and specific diagnostics and (iii) therapeutic agents or vaccines to deliver antiviral agents into human body. In general, nanomaterials such as metal nanoparticles are often less than one micrometer in size, which renders a high surface-to-volume ratio [ 8 ]. Other unique characteristics which include improved solubility and multifunctionality enable effective drug delivery, gene modifications as well as optimal interactions between target analyte and capturing molecules on sensors [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This comprehensive review article focuses on the most recent advances in nanotechnology for COVID-19 based on three main categories: prevention, diagnostics and treatment ( Table 1 , Figure 1 ), providing comprehensive survey about their usability and performance, which is distinct from the existing review papers where only parts of them were discussed [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. In this review, we first discuss the use of various nanomaterials such as metal nanoparticles, carbon-based nanoparticles, magnetic nanoparticles and quantum dots for COVID-19.…”
Section: Introductionmentioning
confidence: 99%